2018
DOI: 10.1016/j.energy.2018.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Minimising the energy consumption of tool change and tool path of machining by sequencing the features

Abstract: and tool change plan will vary based on the different PSFP. This paper firstly aims to un-6 derstand the relationship between the PSFP and the energy consumption of tool change 7 and tool path during the feature transitions. Then, a model is introduced for the single ob-8 jective optimisation problem that minimises the energy consumption of machine tools 9 during the feature transitions which include all the tool path and tool change operations. 10Finally, optimisation approaches including depth-first search a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Garg et al [13] applied a variety of advanced intelligent optimization algorithms to model and analyze the energy consumption in the turning process, and finally found that cutting speed is the main factor affecting the power consumption of the machine tool. Based on the prediction model of material removal energy consumption, Some researchers found that when different processing technology planning and processing were adopted, the machine tool energy consumption was greatly affected [14,15]. Wang et al established a novel drilling energy consumption prediction model, which fully considers the impact of tool wear on energy consumption, and experimental results show that the model has high prediction accuracy [16].…”
Section: Prediction Of Cutting Energy Consumptionmentioning
confidence: 99%
“…Garg et al [13] applied a variety of advanced intelligent optimization algorithms to model and analyze the energy consumption in the turning process, and finally found that cutting speed is the main factor affecting the power consumption of the machine tool. Based on the prediction model of material removal energy consumption, Some researchers found that when different processing technology planning and processing were adopted, the machine tool energy consumption was greatly affected [14,15]. Wang et al established a novel drilling energy consumption prediction model, which fully considers the impact of tool wear on energy consumption, and experimental results show that the model has high prediction accuracy [16].…”
Section: Prediction Of Cutting Energy Consumptionmentioning
confidence: 99%
“…Non-cutting energy consumption. Non-cutting energy consumption can be divided into three parts: tool path energy consumption, tool change energy consumption, and energy consumption of changes in spindle rotation speed (Hu et al, 2018). However, we assume that only one type of tool is used; hence, there is no tool to change the energy consumption in the model.…”
Section: Objective Functionsmentioning
confidence: 99%
“…DFS incorporated Genetic algorithm to discover the optimal processing sequence of features of a part (PSFP) that reduces the feature transitions' energy consumption by 28.60 % [11]. A smaller search space was explored faster with reduced cost by another extended depth-first search (EDFS) algorithm [32].…”
Section: Figure 1 Classification Of Path Planning Approachesmentioning
confidence: 99%